Assessment of CO2 Emission and Energy Reduction on Solid Waste in Jeram Landfill Using Warm Analysis - Abu Hassan, Muhd Hazwan Hisyam; Kasmuri, Norhafezah (International Journal of Integrated Engineering, 2019)
Today, the increasing of solid waste generation became the major issue in Malaysia due to high population growth. The greenhouse emission and high energy consumption resulted from improper management of solid waste have caused a significant effect on the inhabitants and the environment. Hence, it is necessary to develop an integrated solid waste management plan to combat this problem. The challenges are to educate the communities in managing their own waste in a good manner. Recycling awareness among society should also be emphasized to ensure that waste generated can be properly managed. This paper focused on the greenhouse gases (GHG) emissions and energy consumption of municipal solid waste management. The aim of this research is to estimate the income generated from recycling activities from the municipal authority in Shah Alam and Klang district in Selangor. The analysis was done using waste reduction model (WARM) created by the Environmental Protection Agency (EPA), United States. The results indicated that the GHG emission that can be reduced by the Klang authority was 3,024.20 metric tons of carbon dioxide equivalents (MTCO2E) compared to 2,577.80 MTCO2E for Shah Alam authority. The same result has been obtained for the energy emission which indicated the highest saving was 824.90 metric tons of coal equivalents (MTCE) by the Klang authority. However, the Shah Alam authority can only save the amount of 702.80 MTCE. The total incremental of energy used generated by WARM showed that Klang authority can save 23,290.20 million British thermal unit (MBTU) compared to Shah Alam authority of 19,862.80 MBTU. The percentage difference between the Klang authority and the Shah Alam authority in the GHG and energy emission reduction was approximately 14.80%. The total income from recyclable materials for Klang and Shah Alam authority was obtained as RM 918, 638.16. The estimation of GHG emission from both Klang and Shah Alam authority was depending on the solid waste generated and disposal method. In terms of GHG emission, waste separation includes recycling activities could reduce the GHG emission, less air pollution and more environmentally friendly.